The George Gershwin Reader - Gershwin, George 1898-1937; Wyatt, Robert; Johnson, John Andrew (New York Oxford University Press, 2004)
George Gershwin is one of the giants of American music, unique in that he was both a brilliant writer of popular songs and of more serious music. Here, music lovers are reated to a spectacular celebration of this great American composer. The Reader offers a kaleidoscopic collection of writings by Gershwin, as well as those about Gershwin, written by a who's who of famous commentators. More than eighty pieces of superb variety, color, and depth include the critical debate over Gershwin's concert pieces, especially "Rhapsody in Blue" and "An American in Paris." There is a complete section devoted to the controversies over "Porgy and Bess," including correspondence between Gershwin and DuBose Hayward, the opera's librettist, plus unique interviews with the original Porgy and BessTodd Duncan and Anne Brown. Sprinkled throughout the book are excerpts from Gershwin's own letters, which offer unique insight into this fascinating and charming man. Along with a detailed chronology of the composer's life, the editors provide informative introductions to each entry.Here is a book for anyone interested in American music. Scholars, performers, and Gershwin's legions of fans will find it an irresistible feast.
Keywords: 20th Century (1901-2000); Composer; Pianist; USA